Biomarkers of brain injury in patients with stress-related exhaustion: A longitudinal study - Hansson Caroline; Zetterberg Henrik; Snellman Anniina; Blennow Kaj; Jonsdottir Ingibjörg H (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Introduction: Exhaustion Disorder (ED) is a stress-induced disorder, characterized by extreme fatigue, cognitive impairments, and intolerance to stress. These symptoms can be long-lasting, suggesting that the long-term stress may have initiated pathophysiological processes in the brains of patients with ED. The aims of the study were I) to investigate if plasma levels of neurofilament light (NfL), glial fibrillary acidic protein (GFAP), and phos-phorylated tau (p-tau181) differ between patients with ED and healthy controls, and II) to investigate if these differences persist over time.
Method: Plasma NfL, GFAP and p-tau181 were quantified in 150 patients with ED at the time of diagnosis (baseline), 149 patients at long-term follow-up (7-12 years later, median follow-up time 9 years and 5 months), and 100 healthy controls.
Results: Plasma levels of NfL and GFAP were significantly higher in the ED group at baseline compared with controls (mean difference of NfL 0.167, 95 % CI 0.055-0.279; mean difference of GFAP 0.132, 95 % CI 0.008-0.257), while p-tau181 did not differ between the groups. Plasma levels of NfL were significantly lower in the ED group at follow-up than in the same group at baseline (mean difference-0.115, 95 % CI - 0.186- (-0.045)), while plasma levels of GFAP did not differ between the groups, and plasma levels of p-tau181 were significantly higher in the ED group at follow-up than in the same group at baseline (mean difference 0.083, 95 % CI 0.016-0.151). At follow-up, there were no significant differences between the ED group and the control group for any of the proteins.
Conclusion: Plasma levels of NfL and GFAP were increased in patients with ED during the first months of the disease, indicative of axonal and glial pathophysiological processes, but had normalized at long-term follow-up.